Do product quality and perceived suitability influence repurchase intention? - Ediansyah, Ediansyah; Iman Kalis, Maria Christiana; Afifah, Nur; Pebrianti, Wenny; Fitriana, Ana (Junal Ilmu Manajemen, 2024)
This research aims to determine and analyze the direct effect of product quality variables and perceived suitability on repurchase intention and indirect effects through customer satisfaction as a mediator on Indonesian skincare product users. The population in this study are consumers who have purchased and used Indonesian skincare products at least twice in the last 3 months with a minimum age of 17 years and domiciled in Indonesia. The data collection method in this research used a questionnaire, and a sample of 210 respondents was obtained through a purposive sampling technique. The analytical method used in this research is Structural Equation Modeling (SEM) with the AMOS 26 statistical tool. This research shows a significantly positive relationship between product quality, perceived suitability, and consumer satisfaction with the repurchase intention of Indonesian skincare consumers. The perceived suitability felt by consumers is crucial in deciding to continue using a product, so companies need to continue to innovate according to consumer needs.